The Implementation Of Instructional Materials Development Based On Inside Outside Circle (IOC) For Students’ Sociology Education Of Megarezky University - Akhiruddin Akhiruddin; Sujarwo Sujarwo (Universitas of Muhammadiyah Makassar, 2020)
Inside Outside Circle (IOC) is the inner - outer circle group that emphasizes students’ activities to be active in sharing information with their group of friends.This research aimed to develop instructional materials based on inside-outside-circle (IOC) in sociology students of Megarezky University.The development model used is Four-D Model which consists of 4 stages of development namely define, design, develop and disseminate. The instruments of this study used observation, questionnaire, test and documentation. The result of the research showed that IOC model had good quality which met valid, practical, and effective product criteria. It can be concluded that IOC model is one of the improvement from cooperative learning model. Based on practicality, lecturers of teaching and learning can implement IOC learning model in universities (classrooms). then all students achieved individually in teaching and learning courses, it means that students' learning outcomes reached the classical graduation criteria that had been set, that was 100% of students passed. It means that they met the criteria that set the teaching and learning course.It shows instructional materials with IOC model that had been developed consisting of semester lesson plan (RPS), students learning outcomes assessment sheets (LPHBM) that can be used in teaching and learning courses in general and especially in sociology education of Megarezky university.Keywords: Development of Learning Devices, Inside-outside-circle (IOC) model, Instructional Material, Model pembelajaran berbasis Inside Outside Circle (IOC) adalah kelompok dalam-luar lingkaran yang menekankan kegiatan mahasiswa untuk aktif dalam berbagi informasi dengan teman-teman kelompok mereka. Penelitian ini bertujuan untuk mengembangkan perangkat pembelajaran berbasis IOC pada mahasiswa penddikan sosiologi Universitas Megarezky. Model pengembangan yang digunakan adalah Model Empat-D yang terdiri dari 4 tahap pengembangan yaitu mendefinisikan, mendesain, mengembangkan dan menyebarluaskan. Instrumen penelitian ini menggunakan observasi, angket, tes dan dokumentasi. Hasil penelitian menunjukkan bahwa model IOC memiliki kualitas baik yang memenuhi kriteria produk yang valid, praktis, dan efektif. Dapat disimpulkan bahwa model IOC adalah salah satu perbaikan dari model pembelajaran kooperatif. Berdasarkan kepraktisan, dosen pengajaran dan pembelajaran dapat menerapkan model pembelajaran IOC di universitas (ruang kelas). Dan kemudian semua mahasiswa berprestasi secara individu matakuliah Belajar dan Pembelajaran, itu berarti bahwa hasil belajar siswa mencapai kriteria kelulusan klasik yang telah ditetapkan, yaitu 100% siswa lulus, mahasiswa memenuhi kriteria yang menetapkan pengajaran dan pembelajaran tentu saja Ini menunjukkan bahan ajar dengan model IOC yang telah dikembangkan terdiri dari rencana pembelajaran semester (RPS), dan lembar penilaian hasil belajar siswa (LPHBM)) dapat digunakan dalam pengajaran belajar dan pembelajaran pada prodi pendidikan sosiologi Universitas MegarezkyKata Kunci: Pengembangan Perangkat Pembelajaran, Model inside-Outside-Circle (IOC), Bahan Ajar